Effect of the number of daily distributions of solid feed on veal calves’ health status, behaviour, and alterations of rumen and abomasa - Marta Brscic; Luisa Magrin; Paola Prevedello; Andrea Pezzuolo; Flaviana Gottardo; Luigi Sartori; Giulio Cozzi (Italian Journal of Animal Science, 2019)
The research aimed at evaluating the effect of three versus two daily distributions of solid feed on veal calves’ health, behaviour, and rumen and abomasal mucosa alterations with the rationale that three distributions might improve calves’ health and welfare. The study was carried out in two veal calf farms that provided different amounts of solid feed (farm A 200 kg DM/calf; farm B 150 kg DM/calf) during the fattening in addition to liquid milk-replacer. It involved 342 calves in farm A and 108 calves in farm B. The change from two to three solid feed distributions/day started for half calves/farm after the third month of fattening when farm A was feeding 800 g and farm B 600 g DM/calf/day. Health status, blood haemoglobin, and behaviour were assessed on farm at different times. Calves’ carcass weight was recorded and rumens and abomasa were inspected post mortem. Increasing solid feed distributions did not improve calves’ health but it reduced non-nutritive oral behaviours (4.8 versus 3.2 ± 0.4% for two and three distributions/day, respectively) by prolonging the time spent eating solid feed. Carcass weight was similar between treatments. Three daily solid feed distributions did not reduce the prevalence of rumen mucosa hyperkeratinisation and abomasal alterations, worsening the frequency of rumen plaques. As the partition of daily dose of solid feed in three distributions is more time and labour consuming, its benefits addressing only the reduction of non-nutritive oral behaviours seem not sufficient to justify the routinely adoption of this practice by veal producers.